Canción popular, nacionalismo, consumo y política en Chile entre los años 40 y 60 - da Costa Garcia, Tânia [UNESP] (My University, 2009)
Popular urban music is a typically modern cultural event. Its production, distribution and consumption occurred during the process of urbanization of Chile and in a period of growing availability of technological resources. The broadcasting by the mass media allowed popular urban music to reach a larger audience than the local public. Therefore it did not take long time for popular urban music to become a means of cultural homogenization within the parameters of the market system of production and distribution of music, in Chile. This article aims to map the connections between folk music and popular music, with the formation and consolidation of a consumer market for music in Chile. Besides it considers the use of popular music in the forfties and the sixties as a political tool by different groups of the Chilean society, during a time when arts were considered within the controversies about the national identity that arose in different Latin American countries.
Popular music, nationalism consumption and politics in chile during the 1940's and 1960's
Keywords: Chilean popular music; Consumption; Folklore; National identity; Politics